Kanji continuum structure in I Meito Kouryuu no Tanoshimi magazine volume 17 - Delfariyadi, Fahri; Kadir, Puspa Mirani; Soemantri, Ypsi Soeria; Wagiati, Wagiati (Japanese Research on Linguistics, Literature, and Culture, 2022)
This research aims to describe the structure of the kanji continuum within I Meito Kouryuu no Tanoshimi magazine Volume 17. The data source used in this research is I Meito Kouryuu no Tanoshimi Magazine Volume 17 and data form are kanji continuum or kanji sequence. The data is obtained by data recording technique, and the data are classified based on the number of constituent elements in every data, which is 3 and 4 constituent elements. Based on the results of this research, it shows that the kanji continuum is consists of six to nine kanjis, has three or four constituent elements, the three-forming constituent element category is composed of six to seven kanjis, the four-forming constituent element is composed of eight to nine kanjis, it is structured in a head-modifier relationship and the meaning is lexical, and the structure and relation of meaning becomes more complex as the number of letters on the kanji continuum increases.